The Effect of Debt to Equity Ratio, Debt to Asset Ratio, and Risk Based Capital on Return on Asset In General Insurance Companies on The Indonesia Stock Exchange For 2015-2021 Period - Kety Lulu Agustin; Annisa Dewi Dharmmesti; Nurul Musfirah Khairiyah (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2022)
According to the study's findings, the ratios of debt to equity (DER), debt to assets (DAR), and risk-based capital (RBC) all affect return on assets at the same time (ROA). This research was conducted to look at the ratios of risk-based capital (RBC) to return on assets (ROA), debt to equity ratio (DER), and debt to asset ratio (DAR) in general insurance businesses for the years 2015 through 2021. This kind of study employs a quantitative methodology and secondary data sources. Financial statements are the source of the data. The general insurance businesses are the study's population. Analysis is conducted using multiple regression. The IBM SPSS Statistics 25 statistical application is used by the researcher. Debt to Equity Ratio (DER) significantly influences Return on Assets in a favorable way (ROA).